New Neandertal wrist bones from El Sidrón, Spain (1994–2009). Issue 114 (January 2018) - Kivell, Tracy L.; Rosas, Antonio; Estalrrich, Almudena; Huguet, Rosa; García-Tabernero, Antonio; Ríos, Luis; de la Rasilla, Marco
Abstract: Twenty-nine carpal bones of Homo neanderthalensis have been recovered from the site of El Sidrón (Asturias, Spain) during excavations between 1994 and 2009, alongside ∼2500 other Neandertal skeletal elements dated to ∼49, 000 years ago. All bones of the wrist are represented, including adult scaphoids ( n  = 6), lunates ( n  = 2), triquetra ( n  = 4), pisiforms ( n  = 2), trapezia ( n  = 2), trapezoids ( n  = 5), capitates ( n  = 5), and hamates ( n  = 2), as well as one fragmentary and possibly juvenile scaphoid. Several of these carpals appear to belong to the complete right wrist of a single individual. Here we provide qualitative and quantitative morphological descriptions of these carpals, within a comparative context of other European and Near Eastern Neandertals, early and recent Homo sapiens, and other fossil hominins, including Homo antecessor, Homo naledi, and australopiths. Overall, the El Sidrón carpals show characteristics that typically distinguish Neandertals from H. sapiens, such as a relatively flat first metacarpal facet on the trapezium and a more laterally oriented second metacarpal facet on the capitate. However, there are some distinctive features of the El Sidrón carpals compared with most other Neandertals. For example, the tubercle of the trapezium is small with limited projection, while the scaphoid tubercle and hamate hamulus are among the largest seen in other Neandertals. Furthermore, three of the six adult scaphoids show a distinctive os-centrale portion, while another is a bipartite scaphoid with a truncated tubercle. The high frequency of rare carpal morphologies supports other evidence of a close genetic relationship among the Neandertals found at El Sidrón.